Analisis Penerapan Wakaf Polis Di Asuransi Syariah - Nur Dinah Fauziah; Tanto Fatkhurrozi (Universitas Islam Lamongan, 2020)
Economic development in Indonesia has led to the new various products and also the sharia economic development in Indonesia, although it is still relatively young, but the sharia economy continues to thrive with various types of products that can increase the economy. The development of insurance in Indonesia is the form of variation that is able to make Islamic insurance can remain in financial products that are still in demanded by the public, also Waqf polis insurance is a waqf plan by legally inheriting a portion of the asset ownership by waqif when the person dies but can still enjoy the benefits of the assets represented as long as the waqif lives up to the potential and benefits of waqf and its management is productively waqf from the insurance side especially from sharia insurance with the combination of waqf and insurance. This research belongs to the type of literature study research by looking for theoretical references that are relevant to the cases or problems founded and also from several previous studies and from the internet. Productive waqf insurance is successfully integrated so that Indonesia's economy growth through waqf can be realized immediately. Keywords: waqf, sharia insurance, polis wills